The Effect of Using Round-Robin Towards the Students’ Motivation in Reading - Maulia Astuti (Sinar Lima, 2024)
The destinations of the inquiry are anticipated to discover whether or not the utilize of Round-Robin method be able to extend students' inspiration in perusing and to discover the impact of utilizing Round- Robin towards the students' inspiration in perusing the eleventh long- time understudy at SMA Negeri 6 Mataram. The result of this investigation was anticipated to be valuable data within the English instructing and learning preparation, particularly in instructing perusing. This investigation connected the pre-experimental strategy, with two bunches of pre-test and post-test plans. The tests of the inquiry were comprised of 36 understudies from six classes taken from the populace at the eleventh long-time understudy of SMA Negeri 6 Mataram in Scholastic Year 2023/2024. The result of the information investigation appeared that the students' perusing comprehension was affirmed. It may appear from the result that the t-obtained esteem (12.925) was higher than the t-table esteem (2.030). those shown that Ho was rejected and Ha was acknowledged. It implies that the students' perusing comprehension was able to increment by utilizing the Round-Robin technique. Besides that, the result of the result of the questionnaire showed that most understudies concurred and had a positive reaction to perusing by utilizing the Round-Robin procedure. Based on the result of the information investigation over, the analyst then concluded that there was a change of understudies in perusing comprehension, which implies that the Circular Robin procedure can extend students' inspiration in perusing at the eleventh long-time understudy of SMA Negeri 6 Mataram.